The history of EIBA : a tale of the co-evolution between international business issues and a scholarly community - Simões, Vítor; Cantwell, John; Gugler, Philippe (Emerald Publishing Limited, 2024)
The European International Business Academy (EIBA) is a scholarly association that commemorates its 50th anniversary in 2024. Created in December 1974, EIBA is a professional society for academics and others interested in the multidisciplinary field of International Business (IB): it serves as a community network promoting research, interdisciplinary and international research collaboration, global communication, knowledge sharing, life-long learning and, more broadly, the exchange of ideas among its members around the World. EIBA has travelled a long way to attain the status today of one of the most attractive associations in the IB field. The book provides a lively account of how EIBA and this field of scholarship has evolved over these past 50 years. The account is important not just for those who have followed most of EIBA's life, but especially for the younger generation to get acquainted with the roots and the development of the IB field in Europe. Taking a chronological approach, the book highlights, chapter by chapter, the changing character of IB in the real world, the state of IB scholarship in each period, and the growth of the IB scholarly community in Europe as represented by EIBA. Overall, it will examine how these three elements (IB context and actors, the analysis of IB, and the professional community of researchers in Europe and beyond) have co-evolved over time.